2018
DOI: 10.1242/dev.153858
|View full text |Cite
|
Sign up to set email alerts
|

Differential spatial distribution of miR165/6 determines variability in plant root anatomy

Abstract: A clear example of interspecific variation is the number of root cortical layers in plants. The genetic mechanisms underlying this variability are poorly understood, partly because of the lack of a convenient model. Here, we demonstrate that , unlike, has two cortical layers that are patterned during late embryogenesis. We show that a miR165/6-dependent distribution of the HOMEODOMAIN LEUCINE ZIPPER III (HD-ZIPIII) transcription factor PHABULOSA (PHB) controls this pattern. Our findings reveal that interspecie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 54 publications
1
37
0
Order By: Relevance
“…However, since CO2pro: NLS-YFP expression was dramatically decreased in hda19 and we were unable to ascertain the status of JKDpro:JKD-CFP because it was silenced after crossing, we cannot be sure at this time. Several other factors, including SCR, SHR, the BIRDs, and miR165/6, are known to contribute to ground tissue patterning through complex transcriptional regulation, proteinprotein interactions, and protein movement (Cui and Benfey, 2009b;Koizumi et al, 2012;Wu and Gallagher, 2014;Long et al, 2015;Di Ruocco et al, 2018). Thus, the precise role of HDA19 in this network is a subject of future analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, since CO2pro: NLS-YFP expression was dramatically decreased in hda19 and we were unable to ascertain the status of JKDpro:JKD-CFP because it was silenced after crossing, we cannot be sure at this time. Several other factors, including SCR, SHR, the BIRDs, and miR165/6, are known to contribute to ground tissue patterning through complex transcriptional regulation, proteinprotein interactions, and protein movement (Cui and Benfey, 2009b;Koizumi et al, 2012;Wu and Gallagher, 2014;Long et al, 2015;Di Ruocco et al, 2018). Thus, the precise role of HDA19 in this network is a subject of future analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate analysis of Cardamine root GT patterning demonstrated that Cardamine show two cortical layers (an outer and an inner one) originating from a developmental domain of mix cortex and endodermis identity (CEM) absent in Arabidopsis. In this species, the CEI firstly divides asymmetrically giving rise to a cortex layer and a CEM that subsequently divides periclinally originating the endodermis and an inner cortex (figure 2b) [43]. The Cardamine inner and outer cortical layers are patterned by stereotypical division happening during embryogenesis.…”
Section: (D) Mechanisms Of Cortex Proliferation In Species With Multimentioning
confidence: 98%
“…Cardamine additional cortex formation [43]. Intriguingly, in Cardamine, miR165/6 activity is low in the CEM, generating a broader expression domain of PHB that is therefore expressed in this tissue [43].…”
Section: (D) Mechanisms Of Cortex Proliferation In Species With Multimentioning
confidence: 99%
See 1 more Smart Citation
“…The expanded PHB activity domain results in the formation of a cortex/endodermis mixed (CEM) cell. Here, PHB activates CYCD6;1 resulting in a division, and thereby the formation of an additional cortex cell layer ( Di Ruocco et al, 2018 ). Orange highlights indicate differences in expression domains compared to Arabidopsis.…”
Section: The Stele Ensures It Is Surrounded By a Single Guarding Endomentioning
confidence: 99%